Konstitusi dalam Praktik Ketatanegaraan di Indonesia - Virna Septia Anggyamurni; Yusya Rugaya Salsabilah; Ewaldo Duta Salsa (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2020)
A country has the highest legal norms called the Constitution. Undang-undang Dasar Negara Republik Indonesia Tahun 1945 is a written constitution in Indonesia. The Constitution can be used as an absolute grip in the survival of the society, the nation and the state as it is considered as the political picture. A legal force is demonstrated by the existence of a constitution, therefore it must be obeyed and upheld without the slightest deviation. Through a theoretical approach, this paper discusses the history of the development of Indonesian state administration, mostly about the constitution that was once in force. The author concludes that based on the Indonesian Constitutional history there have been several stages of change in the period of 1945 until now. The New Order's political practices caused trauma to the Indonesian people in the existing constitutional, with the idea coming up to amend the Constitution. Changes to the stages of the Constitution in Indonesia include UUD 1945, UUD RIS, UUDS 1950 and back to UUD 1945 with amendments 4 times and is valid until today. Each of these constitutional stages has a unique constitutional model. After UUD 1945 was amended it was clear that democratic life was growing better. Not only that, the progress in the constitutional system is also getting bigger, especially with the existence of a check and balance format.